“My Kidney Disease, My World as an Arena:” Unpacking the Situation of Adolescents from the Perspective of Postmodern Grounded Theory - Ruidiaz Gómez, Keidis Sulay; Cacante Caballero, Jasmín V. (Investigación y Educación en Enfermería, 2024)
Objective. To explore the meanings of quality of life for adolescents with chronic kidney disease (CKD). Methods. This qualitative study was conducted using a grounded theory situational analysis approach, following the interpretive turn. Four in-depth interviews were conducted with adolescents with CKD, five with parents, and four with healthcare professionals (three nurses and one physician). The collected data were analyzed using situational maps, social world/arenas maps, and positional maps, as proposed by Adele Clarke. Results. The characterization of these adolescents’ situations shows that they are the main actors and modify their social role when they suffer from CKD. It is the mothers that traditionally care for them, until they regain their health. The social world map shows the interactions among the worlds of individuals, their families, and the healthcare system, constituting a well-being arena which defines the quality of life for adolescents with CKD. Discursive positions constitute a key element in the discussion concerning the relational dimensions of well-being and the feelings emerging in relation to the disease. Conclusion. For adolescents with CKD, quality of life is defined as the state of well-being emerging from the recognition of their own environment in micro-, meso‑, and macro-systems, which bring together structural (political, cultural, symbolic) elements, discursive constructions, and the integration of interactions in the social arenas, as well as the representation of the main discourses and their positions.